THE ROLE OF LOCAL GOVERNMENTS IN DEVELOPING NATURAL AND CULTURAL TOURISM IN SUKABUMI DISTRICT - Gumilar Mulyana (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2021)
Tourism activities are human activities driven by curiosity and enjoying tourist attractions and tourist attractions without knowing administrative boundaries. Therefore, the concept of integrated regional development can overcome and assist organizational differences between districts into a unity of regional planning and development with tourism activities in Sukabumi Regency. In this research, the method used is a qualitative descriptive approach. Sources of data in this study come from primary data and secondary data. The data collection technique used is field research, such as observation, interviews, and library research. The analysis used by the pen is descriptive-qualitative. The research results on tourism's role in developing tourism potential in the Sukabumi Regency are dominant as a facilitator compared to other parts. This role as a facilitator can be seen mainly in the provision of object infrastructure, which is still largely borne by the Tourism Office. Facilities for distributing stimulant fund assistance for people who want to develop a tourism object, promote tourism objects, and facilities provided to third parties such as investors and tourism entrepreneurs to develop their tourism businesses in Sukabumi Regency.